Ecological stoichiometry comparison of the plant-litter-soil system of Quercus rehderiana in different rocky desertification habitats - Xiaolong Bai; Shun Zou; Tu Feng; Bin He; Wangjun Li (BMC Plant Biology)
Abstract Aims Carbon (C), nitrogen (N), and phosphorus (P) stoichiometry serves as a crucial indicator of interconnected biogeochemical cycles in terrestrial ecosystems, influencing nutrient limitation patterns, elemental balance and coupling, as well as plant adaptation strategies to environmental constraints. However, the interaction mechanisms between plants and soils in karst rocky desertification forests remain poorly understood. This study comparatively analyzes the C, N, and P stoichiometric characteristics of Quercus rehderiana in both rocky and non-rocky desertification forests, aiming to elucidate the nutrient allocation strategies and element coupling mechanisms within rock desertification forest ecosystems. Methods Five 20 m × 20 m plots were respectively established in rocky desertification and non-rocky desertification Quercus rehderiana forests, and each plot was further divided into four subplots of 10 m × 10 m. From three subplots closest to the center, we collected leaf, branch, fine root, litter, and soil samples and measured C, N, and P concentrations. Results The results showed that non-rocky desertification forests exhibited significantly higher P concentrations compared to their rocky desertification counterparts. Conversely, rocky desertification forests showed notably higher C: N and C: P ratios in all plant organs (leaf, branch, root) and litter. The N and P concentrations in Quercus rehderiana were higher in leaves and litter than in branches, which in turn were higher than in roots. The C: N and C: P ratios exhibited the opposite trend, with values following the order: roots > branches > litter and leaves. In rocky desertification forests, P concentration was significantly negatively correlated with the C: N, C: P, and N: P ratios across plant organs, litter, and soil, suggesting a strong coupling mechanism among these biogeochemical indicators. Conclusions This research elucidates the C: N:P stoichiometric characteristics of the Quercus rehderiana plant-litter-soil system across varying rocky desertification habitats. Multivariate analysis indicated that forests in rocky desertification areas maintained strong soil nutrient coupling, whereas non-rocky desertification forests exhibited more pronounced litter decomposition-mediated nutrient coupling. These findings provide important insights for ecological restoration and vegetation management in rocky desertification regions.